The Role of Shariah Supervisory Board in Islamic Social Reporting Disclosure - Listyorini, Inon; Utami, Ristianawati Dwi; Prasojo, Prasojo; Amanda, Anisa Siti (Universitas Padjadjaran, 2024)
Islamic Social Reporting (ISR) is a concept of social responsibility based on Islamic principles, assisting Islamic banks in enhancing transparency, accountability, and stakeholder relations. ISR encourages Islamic banks to increase their sustainable social responsibility to promote Islamic ethics in business practices. This study aims to analyze the impact of Sharia Supervisory Board (SSB) characteristics on ISR disclosure in Islamic banks in Indonesia. The analysis utilizes the unbalanced panel fixed effect model method and involves 15 Islamic banks from 2017 to 2021. The findings confirm that cross-member, expertise, and turnover of SSB have a significant positive effect. In contrast, the size, the education level, and remuneration of SSB do not affect ISR disclosure.